Dyskusja w sprawie wyodrębniania prawa gospodarczego - Bator, Andrzej; Chełmoński, Adam; Gilas, Janusz; Kosikowski, Cezary; Rabska, Teresa; Wasilewski, Andrzej; Włodyka, Stanisław; Żuławska, Czesława (Wydział Prawa i Administracji UAM, 1993)
To the above question, posed to lawyers interested in corporate law, the editors of "Ruch Prawniczy, Ekonomiczny i Socjologiczny" received a number of answers. Though both the substance and the form of answers were very different, they present a very interesting, contemporary characterization of corporate law and the science of corporate law. 1. There seems no doubt that there is a close connection between corporate law and the political and economic system of the state (see in particular: Cz. Żuławska and C. Kosikowski). Despite this dependency (and the resulting correlation between the concept of corporate law and the political and economic system), there is little change as to the theoretical approach to the "nature" of this law and the method of solving this problem. The issue at stake lies not so much in the fact whether corporate law exists, but whether, and to what extent, it constitutes a specialized part of law, and further, whether this part is of a complex character, or whether it can be placed within one traditional branch of law (in favour of the latter view: Cz. Żuławska, against: S. Włodyka), or, finally, whether separate branches of law and/or scientific disciplines (or subdisciplines) should be distinguished, or both separate branches of law and scientific disciplines (thus all other respondents). 2. The most important issue is the argumentation in favour of distinguishing corporate law (A. Bator, A. Chełmoński, S. Włodyka). The existence of this branch of law seems to leave no doubt. However, the reference to the contents of positive law does not allow to answer the issue of distinguishing the said branch of law. The list of legal definitions and notions introduced by particular contemporary legal acts (e.g., "corporate case", "corporate entity", "economic activity", etc.) would not lead to uniform conclusions. The same can be said about the scope of cognition of courts which have jurisdiction to hear corporate cases (Chief Administrative Court, corporate courts, anti-monopoly court). Finally, frequent amendments to legal acts are not in favour of reaching any conclusions in this respect. 3. Against this background, it is maintained that the term "corporate law", with no other qualifications, cannot be a priori considered to be related to private law or both private and public law problems of corporate activity (A. Wasilewski). Besides, treating this branch of law as a specialized part of civil law (Cz. Żuławska) would not allow to encompass the whole sphere of corporate relations. Finally, the existence of specialized parts of administrative and constitutional law fully justifies the presence of the discipline of public corporate law, separate from private law ( T. Rabska, S. Włodyka). 4. No one was not in favour of a concept of the complex discipline. The respondents stressed that the catalogue of "principles of corporate law", elaborated in the past, ceased to exist (Cz. Żuławska). A view prevails that "corporate law" cannot be practiced as one integrated scientific and didactic discipline (A. Chełmoński). One should also refer to legal disciplines distinguished in Western Europe (S. Włodyka). The above fact is also reflected in university curricula in Poland. The justification is simple: specialization is dictated by specific needs of economic activity, requiring a detailed and complex approach and diversified legal solutions. The above opinion is shared also by other authors (Cz. Kosikowski, T. Rabska). However, final concepts presented by the authors are to a great extent determined by legal disciplines they represent. 5. Many respondents stressed that legal norms regulating "economic relations" cannot be regarded as a separate type of legal norms (in particular, A. Bator). Thus, of foremost importance is the subject-matter of regulation. Hence, there appears a basic question, namely whether the subject-matter of corporate law is the regulation by the state of economic relations from the viewpoint of individual rights and interests of corporate entities (C. Kosikowski, T. Rabska, S. Włodyka), or whether the subject-matter of corporate law refers exclusively to civil-law relations between corporate entities, regulated by dispositional legal provisions (Cz. Żuławska). A relatively new trend in Polish law and in the Polish science of law is the concept of public corporate law, the scope of which is wider than, and different from, the traditional administrative corporate law (T. Rabska, C. Kosikowski, S. Włodyka). Its subject-matter would be aimed at the protection of corporate entities, and not at a direct intervention of the state into the economic activity. Such an approach corresponds with the needs of transformation of the economic system of the state and with new aspects of international economic integration (J. Gilas, T. Rabska). Some respondents stressed that economic matters are regulated mostly by means of public-law, rather than civil-law, acts (J. Gilas) and that the most suitable conception of corporate law is the public corporate law (S. Włodyka). 6. The above opinions on corporate law - presented, out of necessity, in a summary and simplified form — do not allow to formulate any more elaborate generalizations as to the branches of law and corresponding legal disciplines. However, those opinions may be considered a very valuable source of reference and a competent introduction to the discussion on the development of the legal system and the science of law. In this sense, the initiative of "Ruch Prawniczy, Ekonomiczny i Socjologiczny" has fully reached its objective.
Discussion on distinguishing corporate law